2019
DOI: 10.3389/fnins.2019.00307
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Training and Transcranial Direct Current Stimulation in Mild Cognitive Impairment: A Randomized Pilot Trial

Abstract: Background Transcranial direct current stimulation (tDCS), a non-invasive stimulation, represents a potential intervention to enhance cognition across clinical populations including Alzheimer’s disease and mild cognitive impairment (MCI). This randomized clinical trial in MCI investigated the effects of anodal tDCS (a-tDCS) delivered to left inferior frontal gyrus (IFG) combined with gist-reasoning training (SMART) versus sham tDCS (s-tDCS) plus SMART on measures of cognitive and neural changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 70 publications
3
66
2
1
Order By: Relevance
“…Mean improvement did not persist on follow-up, also in line with our findings. At odds with our results, Das et al, using a pre-training stimulation approach, showed a negative impact on immediate cognitive performance [46]. Note, though that optimal timing of tDCS application (pre-, during, or post-training) is still an open question and certainly depends on a number of factors, like task, current brain state, or population under study.…”
Section: Effects Of Atdcs On Training Successcontrasting
confidence: 99%
See 1 more Smart Citation
“…Mean improvement did not persist on follow-up, also in line with our findings. At odds with our results, Das et al, using a pre-training stimulation approach, showed a negative impact on immediate cognitive performance [46]. Note, though that optimal timing of tDCS application (pre-, during, or post-training) is still an open question and certainly depends on a number of factors, like task, current brain state, or population under study.…”
Section: Effects Of Atdcs On Training Successcontrasting
confidence: 99%
“…Thus, MCI patients, in whom low memory performance is a hallmark of the clinical symptomatology, may be particularly susceptible to the beneficial effects of atDCS. Encouraging results have been reported for repeated atDCS in MCI due to AD [42,43] and atDCS combined with CT in MCI due to idiopathic Parkinson's disease [44,45], but a negative effect has been reported in a study applying atDCS before CT in MCI due to AD [46]. Conflicting results might result from heterogeneity between stimulation protocols, e.g., application of atDCS before versus during training [38,47].…”
Section: Introductionmentioning
confidence: 99%
“…A total of three studies investigated the effects of tDCS on neurodevelopmental disorders, with two on ADHD [ 53 , 54 ] and one on dyslexia [ 42 ]. Two studies investigated MCI [ 33 , 55 ]. The demographic details, tDCS protocols, clinical/behavioral outcomes, and brain-behavior relationship results are listed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The remaining two studies reported between-group differences in changes in interhemispheric imbalance [ 35 ] and regional cerebral blood flow (rCBF) after active and sham tDCS, respectively. Kim et al [ 35 ] reported that bilateral stimulation significantly normalized the interhemispheric imbalance in the active anodal stimulation group when compared to sham-stimulated individuals, while Das et al [ 55 ] revealed an increase in rCBF in the right medial prefrontal cortex at rest after applying anodal stimulation over the left IFG.…”
Section: Resultsmentioning
confidence: 99%
“…However, the rest of these intervention studies (Cotelli et al, 2014;Fazeli, Woods, Pope, Vance, & Ball, 2019;Fileccia et al, 2019;Huo et al, 2018;Khedr et al, 2014;Manor et al, 2018;Nilsson, Lebedev, Rydström, & Lövdén, 2017;Ownby & Acevedo, 2016) did not observe significant tDCS-associated gains in any EF tests administered in their studies. One study even reported significant EF gains in the sham stimulation group, but not the tDCS group (Das et al, 2019). It should be noted that these studies had relatively small sample sizes (N treatment group ≤ 21), apart from a few exceptions (N treatment group ≥ 30; Huo et al, 2018;Nilsson et al, 2017;Stephens & Berryhill, 2016).…”
Section: Introductionmentioning
confidence: 99%